Comparative Assessment of Efficiency and Obturation Quality of Kedo-S Plus and Kedo-SH Files During Pulpectomy in Primary Mandibular Molars: An Observational Study - Dr. Richa Pathak; Dr. Sukruti Suresh Babu; Dr. Satyanarayana Naidu S; Dr. Ambika Belam; Dr. Chidananda S; Dr. Roli Mathur (The Bioscan, 2025)
Aim: This research aims to evaluate and compare the efficiency and obturation quality of Kedo-S plus and Kedo-SH files during pulpectomy in deciduous molars. Materials and Methods: The study involved children aged 4–8 years who required pulpectomy for thirty deciduous lower molars. They were randomly divided into two groups: Group I used Kedo-SH files, and Group II used Kedo-S Plus files. A stopwatch recorded the instrumentation time, while Coll and Sadrian criteria assessed the obturation quality. Statistical analysis was performed with the independent t-test and Chi-square test. Results: The mean instrumentation time for Group I was 190.1 seconds, significantly longer than Group II's 110.1 seconds, with a p-value of < 0.0001. However, no statistically significant differences were found in obturation quality between the two groups. Conclusion: The Kedo-S Plus group demonstrated reduced instrumentation time compared to the Kedo-SH group while maintaining comparable obturation quality.